Sistem Penunjang Keputusan Pemilihan Tipe Smartphone Terbaik Di Toko DST Shop Menggunakan Metode Simple Additive Weighting (SAW) Berbasis Web (Studi Kasus : DST Shop) - Esternawati Halawa; Hendri Ardiansyah (CV. Multi Kreasi Media, 2023)
Smartphone is an electronic device that has become a necessity in everyday life. There are 7 criteria that can be used as benchmarks to determine the best smartphone. Brand, price, RAM, ROM, camera, battery and layer type each have a weight value. To make it easier for customers to determine smartphones, it is necessary to have a decision support system to assist in evaluating cellphones that meet the criteria. In this study, the Simple Additive Weighting (SAW) method was applied as an alternative system that can be used to determine cellphones based on criteria and weight values. The results of the calculation of the Simple Additive Weighting (SAW) method obtained from 7 criteria and 7 weight values are Battery and Rom being the largest weight values, namely 20%, Price 15%, Brand 10%, Camera 10%, RAM 15%, Screen Type 10% Based on the results of the calculation of the Samsung Vivo Y22 being the best smartphone with a value of 85.